Motivation Levels among Traditional and Open Learning Undergraduate Students in India - Singh, Shashi; Singh, Ajay; Singh, Kiran (International Review of Research in Open and Distributed Learning, 2012)
Motivation plays a crucial role in learning. Motivation energizes the behavior of the individual. It also directs the behavior towards specific goals. It helps students acquire knowledge, develop social qualities, increase initiation, persist in activities, improve performance, and develop a sense of discipline. This paper aims to compare the levels of motivation between students in the open education system (OES) and in the traditional education system (TES) in India. The study further investigates the motivation levels of male and female students in the two systems. An Academic Motivation Scale was prepared and administered on the students of TES (n = 200) and OES (n = 151). Results show that there exist significant differences in the level of motivation between the students of TES and OES. The study concludes that it is the presence or absence of extrinsic motivation which is predominantly responsible for this difference.